2021
DOI: 10.1021/jacsau.1c00258
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Design of Covalent Organic Framework-Based Electrocatalysts

Abstract: Covalent organic frameworks (COFs) are an emerging type of porous crystalline material for efficient catalysis of the oxygen evolution reaction (OER). However, it remains a grand challenge to address the best candidates from thousands of possible COFs. Here, we report a methodology for the design of the best candidate screened from 100 virtual M–N x O y (M = 3d transition metal)-based model catalysts via density functional theory (DFT) and machine learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 35 publications
3
29
0
Order By: Relevance
“…Recently, Deng et al used machine learning to predict the performances of metalated 3D salen-COFs in OER and identified Ni-salen-COFs to be the best candidate. 532 The synthetic experiments well verified the predicted results, and the Nisalen-COF was overall better than the corresponding Co-, Fe-, Cu-, and Zn-based analogs in Tafel slope, charge transfer resistance, and electrochemical double-layer capacitance. This theoretical and experimental study not only develops the synthesis method of metalated COF electrocatalysts, but also provides insights for material design.…”
Section: Electrocatalysissupporting
confidence: 67%
See 1 more Smart Citation
“…Recently, Deng et al used machine learning to predict the performances of metalated 3D salen-COFs in OER and identified Ni-salen-COFs to be the best candidate. 532 The synthetic experiments well verified the predicted results, and the Nisalen-COF was overall better than the corresponding Co-, Fe-, Cu-, and Zn-based analogs in Tafel slope, charge transfer resistance, and electrochemical double-layer capacitance. This theoretical and experimental study not only develops the synthesis method of metalated COF electrocatalysts, but also provides insights for material design.…”
Section: Electrocatalysissupporting
confidence: 67%
“…Theoretical calculations are powerful tools for studying the structure and properties of materials; for example, first-principles calculations, molecular dynamics simulations, and grand canonical Monte Carlo simulations have been applied in the study of the binding sites of light metals in COFs, 402 optimization of the unit cell structure of COFs, 852 prediction of gas adsorption behaviors, 412,873,874 and design and screening of electrocatalysts. 532,875,876 However, due to computational bottlenecks, theoretical simulations are usually performed on fragments of COFs, leading to one-sided conclusions. Moreover, even such degraded theoretical calculations are rarely used to optimize the metalation synthesis conditions, catalyst screening, prediction of electronic properties, and material-biointerface interaction studies, although they are logically feasible and very important.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Salen complexes as active centers are capable of regulating the coordination environment and local structure flexibly with the help of metal ion exchange. [ 33 , 40 ] Therefore, these unique characteristics enable Metal‐Salen COF EDA as a model to be researched structure–activity relationship in electrocatalysis (see Section 3 for an explanation). However, the electrocatalytic performance of Metal‐Salen COF EDA may be limited by conductivity.…”
Section: Resultsmentioning
confidence: 99%
“…A high correlation was shown to govern the relationship of electrostatic interaction and adsorption energy of intermediates. Final screening of material features showed that four intrinsic factors are only required to describe the OER activity of the model catalysts metal-N x O y , while the predictions could be well-correlated with DFT predictions [ 111 ].…”
Section: Optimization Of Materials Synthesis Using High Throughput Sc...mentioning
confidence: 99%